2010
DOI: 10.1007/s00464-010-1217-5
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic cholecystectomy: a systematic review

Abstract: The clinical application of SILC exhibited satisfactory results. Cases of acute cholecystitis and older patients should be approached with caution, whereas improvement of the instrumentation is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
151
2
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(168 citation statements)
references
References 39 publications
7
151
2
8
Order By: Relevance
“…The mean hospital stay was 1.06 days (range 1-4 days). In the review by Antoniou et al [8], SILC was unsuccessful in 9.3 % of the patients. The most common causes for failure were obscure anatomy at the Callot's triangle, inadequate exposure of the Callot's triangle due to insufficient gall bladder retraction and inability to maintain pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 98%
“…The mean hospital stay was 1.06 days (range 1-4 days). In the review by Antoniou et al [8], SILC was unsuccessful in 9.3 % of the patients. The most common causes for failure were obscure anatomy at the Callot's triangle, inadequate exposure of the Callot's triangle due to insufficient gall bladder retraction and inability to maintain pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 98%
“…However, in our study, patients were carefully selected to ensure that difficult cholecystectomies were excluded. A systematic review of 29 studies, including a total of 1,166 patients undergoing SILC, reported intraoperative complication rates up to 20 % with a cumulative rate of 2.7 % [15]. The most common complications reported were gallbladder perforation/bile slippage, hematoma, bile leakage, and residual choledocholithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Antoniou и соавт. [40] анализировали 1166 ХЭ из ЕЛД и определили, что частота осложнений со-ставляет не более 6,2%, время вмешательств -от 30 до 150 мин при средней длительности 70 мин.…”
Section: рис 8 манипуляции «ловкого» мини-робота при трансгастральнunclassified